Reducing Auditory Hypersensitivities in Autistic Spectrum Disorder: Preliminary Findings Evaluating the Listening Project Protocol - Porges, Stephen W.; Bazhenova, Olga V.; Bal, Elgiz; Carlson, Nancy; Sorokin, Yevgeniya; Heilman, Keri J.; Cook, Edwin H.; Lewis, Gregory F. (Frontiers in Pediatrics, 2014)
Auditory hypersensitivities are a common feature of autism spectrum disorder (ASD). In the present study the effectiveness of a novel intervention, the Listening Project Protocol (LPP) was evaluated in two trials conducted with children diagnosed with ASD. LPP was developed to reduce auditory hypersensitivities. LPP is based on a theoretical “neural exercise” model that uses computer altered acoustic stimulation to recruit the neural regulation of middle ear muscles. Features of the intervention stimuli were informed by basic research in speech and hearing sciences that has identified the specific acoustic frequencies necessary to understand speech, which must pass through middle ear structures before being processed by other components of the auditory system. LPP was hypothesized to reduce auditory hypersensitivities by increasing the neural tone to the middle ear muscles to functionally dampen competing sounds in frequencies lower than human speech. The trials demonstrated that LPP, when contrasted to control conditions, selectively reduced auditory hypersensitivities. These findings are consistent with the Polyvagal Theory, which emphasizes the role of the middle ear muscles in social communication.